2017
DOI: 10.1080/00325481.2017.1324228
|View full text |Cite
|
Sign up to set email alerts
|

Assessing outcomes of educational videos in group visits for patients with chronic pain at an academic primary care clinic

Abstract: Group visits providing patient education about CNCP may benefit patients' knowledge about this clinical condition, and was received with high patient satisfaction. Further investigation is needed to evaluate longer-term knowledge retention, sustainability of improvements resulting from the intervention, and longer-term effects of the intervention on functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…Es importante evaluar la satisfacción de los cuidadores para conocer su experiencia en relación a los videos. Se encontraron resultados positivos en otras investigaciones de un solo grupo con pretest y postest (14,23) ; sin embargo, en estudios cuasi-experimentales con grupo control no equivalente, los videos no han demostrado superioridad sobre otros métodos, por ejemplo, el agregar videos a un enfoque educativo integral no cambia el nivel de satisfacción (24) , ni los cuidadores notan diferencias entre la utilidad de los videos o instrucciones en papel (25) .…”
Section: Discussionunclassified
“…Es importante evaluar la satisfacción de los cuidadores para conocer su experiencia en relación a los videos. Se encontraron resultados positivos en otras investigaciones de un solo grupo con pretest y postest (14,23) ; sin embargo, en estudios cuasi-experimentales con grupo control no equivalente, los videos no han demostrado superioridad sobre otros métodos, por ejemplo, el agregar videos a un enfoque educativo integral no cambia el nivel de satisfacción (24) , ni los cuidadores notan diferencias entre la utilidad de los videos o instrucciones en papel (25) .…”
Section: Discussionunclassified
“…Each video was 10 minutes long and educated patients on pain management and pain medications. At the end of the study, the patients' knowledge of pain was improved, but no impact was observed on patients' functional status 27 (Table 3). Five studies reported the impact of pharmacist intervention on pain intensity.…”
Section: Intervention Through Educational Videomentioning
confidence: 98%
“…Pain measurement tools used in these studies were the Chronic Pain Grade Scale (CPGS), 18,28 Numeric Pain Rating Scale (NPRS), 15,26 Western Ontario and McMaster Universities osteoarthritis index (WOMAC), 16,17 Brief Pain Inventory (BPI), [23][24][25] pharmacotherapeutic pain inventory, 20 and the Pain, Enjoyment of Life and General Activity score (PEG). 27 3.2 | Quality of studies…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations